Capturing reality: Navigating photographic realism in Mohsin Hamid’s Exit West (2017) - Ismail, Khaleel; Alhaisony, Anas (Research Journal in Advanced Humanities, 2024)
This paper aimed to explore the complexities that invoked colonial history and its connection to the contemporary contexts marked by multiculturalism, the war on terror, identity disintegration, displacement, and immigration. It investigated the intricate interplay between photographic realism and contemporary themes within Mohsin Hamid’s novel “Exit West.” The study delved into the meticulous portrayal of migration, geopolitical landscapes, counterterrorism measures, and the influence of digital technology within the narrative. By drawing parallels between Hamid’s prose and photographic realism, the analysis focused on the nuanced exploration of displacement and conflict. The examination of magical doors as a literary device akin to photographic realism revealed their role in capturing the instability of geopolitical structures and disrupting conventional borders. Photographic realism was adopted as a literary theoretical framework. This research contributed to a deeper understanding of how Hamid’s novel served as a critical commentary on the multifaceted challenges within the global human experience, emphasizing the relevance of photographic realism in contemporary literary analysis. After a thematic analysis of the primary text, it was concluded that the novel was a critical portrayal of migrant labor as a commodity, cosmopolitanism, contemporary sociocultural and geopolitical dilemmas, the exploitative nature of the state’s projects, and interracial integration.